A universal growth method for high-quality phase-engineered germanium chalcogenide nanosheets. Issue 9 (8th February 2023) - Qu, Junyu; Liu, Chenxi; Zubair, Muhammad; Zeng, Zhouxiaosong; Liu, Bo; Yang, Xin; Luo, Ziyu; Yi, Xiao; Chen, Ying; Chen, Shula; Pan, Anlian
Abstract : Germanium chalcogenide nanosheets with controllable phase transition are synthesized by a hydrogen-mediated CVD strategy. The systematic investigation can facilitate researchers to screen reasonable materials to achieve different functions. Abstract : Low-dimensional group IV–VI metal chalcogenide-based semiconductors hold great promise for opto-electronic device applications owing to their diverse crystalline phases and intriguing properties related to thermoelectric and ferroelectric effects. Herein, we demonstrate a universal chemical vapor deposition (CVD) growth method to synthesize stable germanium chalcogenide-based (GeS, GeS2, GeSe, GeSe2 ) nanosheets, which increases the library of the p-type semiconductor. The phase transition between different crystalline polytypes can be deterministically controlled by hydrogen concentration in the reaction chamber. Structural characterization and synthesis experiments identify the behavior, where the higher hydrogen concentration promotes the transiton from germanium dichalcogenides to germanium monochalcogenides. The angle-polarized and temperature-dependent Raman spectra demonstrate the strong interlayer coupling and lattice orientation. Based on the optimized growth scheme and systematic comparison of electrical properties, GeSe nanosheet photodetectors were demonstrated, which exhibit superior device performance on SiO2 /Si and HfO2 /Si substrate with a high photoresponsivity up to 10 4 A W −1, fast response time less than 15 ms, and high mobility of 3.2 cm 2 V −1 s −1, which is comparable to the mechanically exfoliated crystals. Our results manifest the hydrogen-mediated deposition strategy as a facile control knob to engineer crystalline phases of germanium chalcogenides for high performance optoelectronic devices.